Undernutrition and short duration of breastfeeding association with child development: a population-based study - Hermano A.L. Rocha; Luciano L. Correia; Álvaro J.M. Leite; Sabrina G.M.O. Rocha; Márcia M.T. Machado; Jocileide S. Campos; Antonio J.L.A. Cunha; Anamaria C. e Silva; Christopher R. Sudfeld (Elsevier, 2022)
Objective: To explore the relationship of undernutrition and the short duration of breastfeeding with child development of children 0-66 months of age residing in Ceará, Brazil. Methods: The authors of the present study utilized population-based data from children enrolled in the Study on Maternal and Child Health in Ceará, Brazil (PESMIC). Children's development was assessed with the Ages and Stages Questionnaire third version, validated in Brazil. Undernutrition was accessed through anthropometric measures obtained by trained staff. Breastfeeding information was obtained through the mothers' report and confirmed in the child's governmental booklet. The authors used logistic regressions adjusted for sample clusters used in PESMIC design in a theoretical model for known determinants of child development following the World Health Organization nurturing framework. Results: A total of 3,566 children were enrolled in the sixth PESMIC study and had their development assessed. The authors found that 8.2%, 3.0%, 2.1%, and 3.6% of children were stunted, underweight, or wasted, at the time of the interview, respectively. All studied factors were associated with a higher prevalence of child development impairment in at least one of the assessed domains. Underweight was the factor with the strongest effect, with an adjusted odds ratio (AOR) of 4,14 (2,26-7,58), p < 0.001. Breastfeeding for up to two months compared to more than six months (AOR 2,08 (1,38-3,12)) was also associated. Conclusions: The authors found that undernutrition and short duration of breastfeeding are associated with development outcomes among Brazilian children. As a result, integrated nutritional programs may improve child development outcomes.